Defining "Battleship Grey". (2nd January 2020) - Croft, Paul
ABSTRACT: This article will examine the definition of 'Battleship Grey' and establish its origin earlier than current thinking. Battleship Grey is widely used as a generic descriptor for virtually any shade of grey, but a recent examination of the last two remaining warships from the First World War has provided a unique opportunity to precisely define this colour for the first time. Specifically, the analysis of two local phenomena: the dialogue between a group of naval officers discussing the efficacy of using grey paint as an effective camouflage colour and the materials analysis of the remaining historic paint layers on both vessels. These local developments challenge the existing historiography and demonstrate a need for naval concealment emerged long before our current perception of the origins of naval camouflage.